2002
DOI: 10.1080/03079450220136567a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an attenuated anticoccidial vaccine and an anticoccidial drug programme in commercial broiler chickens in Italy

Abstract: A live attenuated anticoccidial vaccine (Paracox) was compared with a nicarbazin-monensin anticoccidial drug shuttle programme in three crops of Italian broilers, comprising a total of 290 405 chickens. All birds received the antibiotic growth promoter avilamycin. No coccidiosis was evident during the trials, but the occurrence of oocysts in the litter demonstrated that a natural challenge was present. Vaccinated birds consistently performed at least as well as those treated with the anticoccidial drug shuttle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 11 publications
2
24
0
2
Order By: Relevance
“…The results of the current study indicate that vaccination with a nonattenuated, live oocyst vaccine for the control of coccidiosis does not result in rearing broilers with diminished growth parameters compared with broilers fed salinomycin, provided vaccination is coupled with an appropriate dietary program. These results are in agreement with the report of Williams and Gobbi [12], although these authors observed that vaccination significantly increased broiler BW compared with a medication shuttle program. Body weights of vaccinated broilers were numerically higher in the current study at the termination of the trial, although statistical significance was not observed.…”
Section: Mortality-corrected Fcrsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the current study indicate that vaccination with a nonattenuated, live oocyst vaccine for the control of coccidiosis does not result in rearing broilers with diminished growth parameters compared with broilers fed salinomycin, provided vaccination is coupled with an appropriate dietary program. These results are in agreement with the report of Williams and Gobbi [12], although these authors observed that vaccination significantly increased broiler BW compared with a medication shuttle program. Body weights of vaccinated broilers were numerically higher in the current study at the termination of the trial, although statistical significance was not observed.…”
Section: Mortality-corrected Fcrsupporting
confidence: 82%
“…Other researchers have reported negative effects on cumulative broiler performance when using live oocyst vaccines compared with anticoccidial use, as evidenced mainly by reduced final BW [9,10] and increased FCR [10,11]. Other investigations, however, contradict these cited reports, indicating that vaccinated broilers have performed similarly to, if not better than, medicated broilers [6,12], and that vaccination can lead to significantly lower mortality rates compared with medication [11]. Previous research has indicated that varying dietary protein levels can positively influence performance during clinical coccidial infection [13].…”
Section: Description Of Problemmentioning
confidence: 55%
“…Sabe-se que a vacina comercial contra coccidiose utilizada é composta de baixas doses de oocistos vivos, e foi observado que mesmo utilizando-se 10 vezes a dose recomendada pelo fabricante não houve grandes efeitos desta vacina sobre o desempenho de frangos de corte. Estes resultados podem ser comparados a outros já descritos na literatura (Williams & Gobbi 2002, Lee Kyung-Woo et al 2013, os quais não observaram efeito negativo no desempenho de aves vacinadas com vacinas vivas contra coccidiose em doses recomendadas pelo fabricante. Por outro lado, as dietas utilizadas no presente estudo eram à base de milho e soja e, já foi descrito, que frangos reagem menos severamente à infecção por Eimeria quando alimentados com rações à base de milho, quando comparados a frangos alimentados com ração à base de trigo (Williams 1992).…”
Section: Discussionunclassified
“… ðåçóëüòàòå ïîëó-÷åííîãî îò ìàòåðåé ïàññèâíîãî èììóíèòåòà, ó öûïëÿò íà-áëþäàåòñÿ ìåíåå îáèëüíîå âûäåëåíèå îîöèñò íå òîëüêî E.maxima, íî è E.acervulina, E.tenella. Äàííîå îòêðûòèå áûëî ïîðàçèòåëüíûì, òàê êàê îíî áóêâàëüíî îïðîâåðãëî äîãìó î âèäîñïåöèôè÷íîì èììóíèòåòå ïðîòèâ ýéìåðèé, ïî êðàéíåé ìåðå, ïîñëå åñòåñòâåííîãî çàðàaeåíèÿ [10]. Îäíàêî íà äàííûé ìîìåíò íà òåððèòîðèè ÐÔ îíà íå ïðèìåíÿåòñÿ, â ñâÿçè íå òîëüêî ñ âûñîêîé ñòîèìîñòüþ âàêöèíû, íî è ñîìíèòåëüíîñòüþ òåîðåòè÷åñêîé îáîñíîâàííîñòè åå ýô-ôåêòèâíîñòè.…”
Section: íàïðàâëåíèå ñîçäàíèÿ ìîëåêóëÿðíûõ âàêöèíunclassified